2009
DOI: 10.1095/biolreprod.108.069575
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Human Chorionic Gonadotropin Is Expressed and Produced in Human Secretory Endometrium During the Normal Menstrual Cycle1

Abstract: The objective of this study was to determine whether beta human chorionic gonadotropin (hCG) (CGB) subunits and alpha hCG (CGA) subunits are expressed and the hCG dimer is produced in normal human cyclic endometrium. Endometrial specimens were collected for histological dating from women undergoing treatment in our division of human reproduction. RNA from normal secretory endometrium was extracted, and CGB and CGA gene expression was assessed by semiquantitative PCR. Adequate secretory endometrial specimens we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 72 publications
4
39
0
1
Order By: Relevance
“…Recently, we confirmed both CGA mRNA and CGB mRNA gene expression, detected the CGB and CGA subunits and dimeric hCG protein isoforms by electrophoretic separation, measured the hCG and CGB hormone concentrations in endometrial homogenates, and immunohistochemically characterized increases in hCG production in synchrony with the transformation of the secretory endometrium [24]. We found that glandular hCG release is diminished or absent, respectively, in dyssynchronously transforming or nontransforming secretory cycle phase endometria.…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…Recently, we confirmed both CGA mRNA and CGB mRNA gene expression, detected the CGB and CGA subunits and dimeric hCG protein isoforms by electrophoretic separation, measured the hCG and CGB hormone concentrations in endometrial homogenates, and immunohistochemically characterized increases in hCG production in synchrony with the transformation of the secretory endometrium [24]. We found that glandular hCG release is diminished or absent, respectively, in dyssynchronously transforming or nontransforming secretory cycle phase endometria.…”
Section: Introductionmentioning
confidence: 55%
“…A total of 581 patient endometrium samples used in our recent study [24], consisting of a variety of normal, dyssynchronous, or missing endometrial secretory transformation specimens, were also analyzed histologically according to our endometrium score parameters proposed in that study (glandular shape, glandular nucleus, stromal differentiation, leukocyte number; each scored 1-6 and summarized). After this analysis only the 145 patient samples identified as normal, synchronously transformed secretory endometria were selected and included in the present study.…”
Section: Human Subjects and Tissue Processingmentioning
confidence: 99%
See 3 more Smart Citations